Clinical prevalence and associated intraoperative surgical complications of reproductive tract lesions in pot‐bellied pigs undergoing ovariohysterectomy: 298 cases (2006–2016). (23rd December 2017) - Cypher, Elizabeth; Videla, Ricardo; Pierce, Rebecca; Snowden, Robert T; Sexton, Jennifer Ann; van Amstel, Sarel
Abstract : To address the current dearth of clinically relevant publications regarding ovariohysterectomy (OVH) in the domestic pot‐bellied pig (PBP), the present study aims to report prevalence of uterine lesions, intraoperative complications, and short and long‐term survival in this species (n=298). Prevalence of lesions included uterine neoplasia 11.4 per cent (34/298), pyometra 1.6 per cent (5/298) and cystic endometrial hyperplasia 5 per cent (15/298). Pigs at least six years of age were statistically more likely to have a uterine lesion (less than P=0.001). Smooth muscle tumours represented the most frequent neoplasm. Haemorrhage was the most common intraoperative complication in 23 per cent (8/34) of pigs with neoplasia. Pigs without reproductive tract lesions were statistically more likely to survive to hospital discharge than those with lesions (P=0.001). Short‐term survival, defined as survival to hospital discharge, of pigs with reproductive tract lesions was 89 per cent (48/54). Pigs with pyometra were least likely to survive to discharge 60 per cent (3/5). Long‐term survival (≥1 year) was 93 per cent (14/15) for pigs with neoplasia. Practitioners should be aware of significantly higher rate of neoplastic and inflammatory diseases in PBP at least six years of age. To minimise morbidity and mortality in PBP undergoing OVH, the present study suggests the procedure should be performed prior to six years of age.